Wong Solo Restaurant Service As A Provider Of Processed Chicken Meat To Customer Satisfaction - Sandiah, Natsir; Reni, Wa; Sani, La Ode Arsad; Munadi, La Ode Muh (Pascasarjana Universitas Sulawesi Tenggara, 2021)
The development of poultry farming business is increasing rapidly and contributes greatly in the fulfillment of protein needs. The business sector of processed chicken meat such as cafes, restaurants, and restaurants and sea food to meet the needs of consumers. The research aims to analyze the type of service in influencing the satisfaction of consumers of Wong Solo Kendari Branch by using survey methods and using accidental sampling techniques as many as 60 respondents. It is then analyzed using multiple linear regression tests. The results showed physical evidence, reliability, responsiveness, service assurance, and caring together have a very real effect on consumer satisfaction (p<0.01) in Wong Solo restaurants and factors that correlate positively to customer satisfaction are responsiveness, service assurance and care, while variables that correlate negatively to consumer satisfaction are physical evidence and reliability. Variable concern partially affects consumer satisfaction (P<0.01).